Interpretation criteria for California Mastitis Test in the diagnosis of subclinical mastitis in cattle - Gómez-Quispe, Oscar Elisban (2015)
The study was conducted in the district of Tamburco (Abancay, Apurimac, Peru) with the aim of comparing interpretation criteria of California Mastitis Test (CMT) in the diagnosis of subclinical mastitis in cattle. Two hundred and nine cows from a population of 459 hand-milked cows belonging to 95 breeders were used. A total of 828 functional mammary quarters were evaluated and the main criteria for CMT interpretation were estimated. The prevalence of subclinical mastitis in cows was 72.3 and 65.6%, and in total mammary quarters was 48.7 and 42.3% with and without considering traces as positives respectively, and without statistical difference. The estimated prevalence in individual mammary quarters varied between 48.3 to 49.3% and depending of the mammary quarter between 40.0 to 45.5% with and without considering traces as positives respectively (p<0.05). More intense positive reaction was found in grades 1, 2 and 3 crosses and lower in the trace grade. Subclinical Mastitis Index (IMSC) was 1.30 and the Low Risk - High Risk Index (I BR/AR) was 2.71. It was concluded that the CMT interpretation criteria for subclinical mastitis have similar meanings, but each provides specific details of the disease; besides, the IMSC and I BR/HR indices provide useful information on the dynamics of subclinical mastitis.